Effects of different extracts of curcumin on TPC1 papillary thyroid cancer cell line - Angelica Perna; Antonio De Luca; Laura Adelfi; Tammaro Pasquale; Bruno Varriale; Teresa Esposito (BMC, 2018)
Abstract Background The thyroid gland is one of the largest endocrine glands in the body. The vast majority of TCs (> 90%) originate from follicular cells and are defined as differentiated thyroid cancers (DTC) and the two histological subtypes are the papillary TC with its variants and the follicular TC. Curcumin possesses a wide variety of biological functions, and thanks to its properties, it has gained considerable attention due to its profound medicinal values (Prasad, Gupta, Tyagi, and Aggarwal, Biotechnol Adv 32:1053-1064, 2014). We have undertaken the present work in order to define the possible role of curcumin in modulating the genetic expression of cell markers and to understand the effectiveness of this nutraceutical in modulating the regression of cancer phenotype. Methods As a template we used the TPC-1 cells treated with the different extracts of turmeric, and examined the levels of expression of different markers (proliferative, inflammatory, antioxidant, apoptotic). Results Treatment with the three different curcumin extracts displays anti-inflammatory, antioxidant properties and it is able to influence cell cycle with slightly different effects upon the extracts. Furthermore curcumin is able to influence cell metabolic activity vitality. Conclusions In conclusion curcumin has the potential to be developed as a safe therapeutic but further studies are needed to verify its antitumor ability in vivo.